Cutting the Difficult Papilla: Ancillary Techniques in the Performance of Endoscopic Sphincterotomy - Claude Liguory; Jean Francois Lefebvre; Didier Bonnel; Gary C Vitale (Canadian Journal of Gastroenterology)
Of 1040 endoscopic sphincterotomies performed over a five year period, standard papillotomy was possible in 874 (84%). In 166 cases (16%) a difficult papilla was encountered requiring nonstandard techniques of precutting, transpapillary guided endoscopic sphincterotomy, transhepatic guided endoscopic sphincterotomy and percutaneous transhepatic sphincterotomy. The technique first attempted in these 166 cases was successfully completed in 154 (93%). Among the 135 cases with intradiverticular papillas, successful papillotomy was achieved in 125 (92.7%). Early complications of standard endoscopic sphin-.lerotomy included bleeding, perforation, pancreatitis and cholangitis, comprising 4.3% of the 1040 sphincterocomies. There were five deaths (mortality rate 0.5%) and laparotomy was required in six patients (0.6%). Conditions contributing to complications included an intradiverticular papilla and precutting. Evaluation of endoscopic sphincterotomy by transpapillary or transhepatic routes guided by guidewire or drain placement revealed complication rates of 6.6 and 10.6%, respectively. Of the patients with histories of gastric resection and Billroth II anastomoses, standard sphincterotomy was possible in 15 (55.5%); in two cases the papilla was unapproachable endoscopically, requiring use of percutaneous transhepatic sphincterotomy. The percutaneous transhepatic sphincterotomy without endoscopic control is felt to be a higher risk procedure and should be reserved for rare indications. Appropriate use of these techniques should allow performance of endoscopic sphincterotomy in almost all clinical settings.